Characteristics of adhesive properties of lactobacillus - clinical isolates and components of biological products - Lavryk, G (Annals of Mechnikov’s Institute, 2020)
Lactobacilli detected in all biotopes of digestive tract, starting from the mouth and ending with the colon, is the dominant flora of vaginal biotope. Their adhesiveness to epithelial cells leads to survive in conditions of microorganism biotopes and to form biofilm, thus mediating passive antagonism against conditionally pathogenic bacteria. Colonization resistance provides a set of mechanisms that provide individual anatomical stability and normal microflora. It is experimentally confirmed that lactobacilli provide biotopes colonization resistance of the human body due to competitive inhibition and coagregation of allochthonous microorganisms. It is important to consider the fact that probiotics should not compete with autochthonous microflora, which is always more physiological for each individual than most valuable exogenous bacteria, even with the greatest potential beneficial properties. The probiotic activity should be directed to the main target bacterial therapy, which is to restore physiological ecological community. The aim of research was to compare the adhesive properties of lactobacilli - clinical isolates of probiotic preparations and ingredients to the buccal epithelium cells and erythrocytes 0 (1) of the blood group system AB0 person. Materials and methods. The object of the research were clinical strains of Lactobacillus spp. selected from the mouth, intestines, vagina healthy people. At the the species identification of lactic acid bacteria were taken into account morphological and cultural properties, aerotolerance. The carbohydrate profile was determined using the test system API-50SN L (Bio-Merieux), lack of catalase activity. The ability of allocated bacteria to adhesion were observed in erythrocytes 0 (1) blood and buccal epithelium cells by human Brilis VI and oth. For comparison were used probiotic strains L. rlantarum 8P-A3, L.acidophilus KS 400, Lactobacillus reuteri DSM 17938. The effectiveness of adhesion was assessed by index microorganism adhesion (I) - the average number of microorganism on one epithelial cells that is involved in the adhesion - determined by the formula = IAM (SPA × 100) / K. We determined this rate when calculating under the microscope 50 buccal cells/erythrocytes. Results and discussion. We received 102 strains of lactobacilli including 32 oral, 41 intestinal and 29 vaginal isolates. In species composition among isolates from all biotopes were dominated such Lactobacillus species: L.acidophilus (15 strains from the mouth, intestine – 12, vaginal - 9), respectively L.plantarum (4, 6, 3), L.fermentum (5, 10, 8), L. rhamnosus (4, 3, 6), L.casei (4, 7, 3). The only type L.brevis (3) just stood out from the intestine. During the research it was found that indicators of lactobacilli adhession to buccal epithelium cells and erythrocytes 0 (1) blood are different between each other. Almost all of lactobacilli isolates showed high activity and high adhesive on the buccal epithelium. Highly adhesive appeared to be vaginal lactobacilli isolates 4,19±0,06. Among intestinal isolates the most pronounced adhesion to buccal epithelial showed L.casei 4,66±0,04, L.acidophilus 4,13±0,08. In isolated mouthes of L.acidophilus and L.plantarum adhesive activity almost identical (4,12±0,07 and 4,10±0,08). It should be noted that the level of adhesion of lactobacilli to red blood cells is much lower than the buccal epithelium. Thus, the adhesion index of L.acidophilus, which were isolated from different biotopes to the buccal epithelium was 4,15±0,03, and - according to erythrocytes 2,50±0,01 (p>0,05). Almost all strains isolated from the intestines and vagina showed high adhesiveness to erythrocyte 2 ± 0,03 and 2,14 ± 0,02 accordingly; except L.casei of intestinal origin and L.plantarum, isolated from the vagina, which amounted IAM 3 ± 0,03 and 2,53 ± 0,08. In probiotic strains of Lactobacillus was observed a similar situation, but with a less expressed difference in the adhesion index on buccal epithelium and erythrocytes. The greatest adhesion observed in L.reuteri DSM 17 938 5,18± 0,03. Conclusion 1. There were isolated from different biotopes of the human body 5 dominant species of lactobacilli: L. acidophilus, L. fermentum, L. casei, L. plantarum, L. rhamnosus. L.brevis was only distinguished from the intestine. 2. High adhesiveness was observed for strain L. casei, L.plantarum, isolated, both from the mouth and from the vagina, indicating a high affinity of shell structures specified types of lactobacilli in the appropriate structures of buccal epithelium. The highest adhesion to isolates from the digestive tract to found types L.casei. Received direct correlative relationship between an index of adhesion on buccal epithelium and erythrocytes. These data confirm that the adhesiveness is more strain feature than species. 3. In the absence of clinical manifestations of dysbiotic changes (especially in infants)to limit the use of probiotic preparations "prophylactically" as high adhessive probiotic strains may displace or inhibit the formation of its own microflora. 4. It is an open question of the effectiveness of some bio therapeutic drugs, the result of which is to replace Lactobacillus auto strains to the probiotic strains in natural habitats of the human body.